Intensity of Physical Activity in Physical Education Classes and School Recesses and Its Associations with Body Mass Index and Global Fitness Score in Spanish Schoolchildren - Garcia-Hermoso, A (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Background: Examining the association between excess weight or physical fitness and intensity of physical activity (PA) during Physical Education (PE) classes or school recesses and in children could be of great interest and importance, especially for future intervention programs or public policies related to PA. The aim of this study was to explore the association between intensity of PA in PE classes or school recesses and excess weight or global physical fitness in a sample of Spanish schoolchildren. Methods: We performed a cross-sectional study in the Valle de Ricote (Region of Murcia, Spain). A final sample of 350 Spanish schoolchildren between 6 and 13 years of age was included from six different schools. Intensity of PA during PE classes and recesses was assessed by the Physical Activity Questionnaire for Older Children (PAQ-C). To assess physical fitness, the extended ALPHA fitness test battery was used. Body mass index (z-score) was calculated following the age-and sex-specific thresholds of the World Health Organization. Results: Both body mass index (z-score) and Global Fitness Score (z-score) were lower in schoolchildren engaging in high intensity of PA in both PE lessons and school (p < 0.05 for all). Lower odds of having excess weight were found in those who reported high intensity of PA in both PE classes and school recesses (OR = 0.54; CI 95%, 0.30–0.96). In these same participants, higher odds of being in the high Global Fitness Score tertile were found (OR = 1.96; CI 95%, 1.01–3.85). Conclusions: Our study showed that higher intensity of PA in PE classes and school recesses was associated with lower excess weight and higher global physical fitness. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.